Physico-chemical properties and fractions of organic carbon and nitrogen in the soil under twenty-year-old tree species - Singh, Baljit; Singh, Sunpreet; Chaudhary, Smriti (Indian Journal of Agroforestry, 2021)
A study was conducted to evaluate the effect of different multipurpose tree species on soil physico-chemical properties and pools of soil organic carbon (OC) and nitrogen. Depth wise (0-15, 15-30, 30-45 and 45-60 cm) soil samples were taken from twenty-year-old plantations of Eucalyptus tereticornis (eucalyptus), Azadirachta indica (neem), Melia azedarach (dek), Dalbergia sissoo (shisham), Albizia lebbeck (siris), Leucaena leucocephala (subabul) and Acacia nilotica (kikar) spaced at 6 m Ã— 3 m and adjoining open area (control) at PAU Regional Station, Bathinda. Soil pH and bulk density were lower under trees than control. Water holding capacity and cation exchange capacity increased significantly under trees over control in all the soil depths. The increase was higher under siris and shisham than other species. Soil OC and its pools increased significantly under tree species over control and these were higher in upper soil than the lower depths. The increase in soil OC stock was highest under siris (145%), followed by kikar (129%) and the lowest under eucalyptus (101%) over control (8.09 t ha-1) in the surface soil depth. Very labile, labile, less labile as well as recalcitrant fractions were highest under siris primarily in 0-15 and 15-30 cm soil depths. Total, ammonium and nitrate N were significantly higher under subabul, shisham, kikar and siris than other tree species and control. Therefore, siris, subabul, shisham and kikar had higher potential to improve soil health in terms of improvement in soil properties, organic carbon and nitrogen content of the soil.